2018
DOI: 10.1002/jsfa.9143
|View full text |Cite
|
Sign up to set email alerts
|

Marine macroalgae as sources of protein and bioactive compounds in feed for monogastric animals

Abstract: Marine macroalgae are considered as promising sustainable alternatives to conventional terrestrial animal feed resources. The advantages include high growth rate, potential cultivation in saltwater, and no occupation of arable land. Macroalgae are broadly classified as brown (Phaeophyta), red (Rhodophyta) and green (Chlorophyta) algae, and are a diverse group of marine organisms. The nutritional value of macroalgae is highly variable. The protein and essential amino acid content can be low, especially in brown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(235 citation statements)
references
References 129 publications
(342 reference statements)
7
206
0
2
Order By: Relevance
“…Seaweeds are considered a good source of protein, as they contain all essential amino acids, acidic amino acids, and conditional essential amino acids (Tanna & Mishra, ). Amino acid profiling of selected seaweeds confirmed that they contain higher concentration of some essential amino acids than the milk and egg protein consumed worldwide (Øverland, Mydland, & Skrede, ). There are numerous reports on the amino acid composition of seaweed species from various locations.…”
Section: Discussionmentioning
confidence: 93%
“…Seaweeds are considered a good source of protein, as they contain all essential amino acids, acidic amino acids, and conditional essential amino acids (Tanna & Mishra, ). Amino acid profiling of selected seaweeds confirmed that they contain higher concentration of some essential amino acids than the milk and egg protein consumed worldwide (Øverland, Mydland, & Skrede, ). There are numerous reports on the amino acid composition of seaweed species from various locations.…”
Section: Discussionmentioning
confidence: 93%
“…A major component of brown seaweed cell walls is a salt form of alginic acid, alginate with the content ranging from 140-400 g/kg DM [30]. Brown seaweed walls are also rich in fucoidans, which are saccharide units with different degrees of sulphation.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Diatoms structural characteristics, and thus the different types of functional components have various biological applications. The fucoidan content varies in relation to seaweed species and season, although the content ranges from 20 to 200 g/kg DM, with the highest value in Fucus vesiculosus [17,30,31]. Laminarin, composed of (1,3)-b-D-glucopyranose residues, is the main reserve carbohydrate of brown seaweeds with a content ranging from 0 to 300 g/kg DM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations